ANALISIS VALIDASI SOAL TES HASIL BELAJAR PADA PELAKSANAAN PEMBELAJARAN BAHASA ARAB DI PUSAT PENGEMBANGAN BAHASA (P3B) UIN SUSKA RIAU - Fatimah Depi Susanty (Kutubkhanah, 2016)
One of the main conditions that must be fulfilled related to the management quality system ISO 9001:2000 is the verification and calibration of the learning achievement test. This research aimed at finding the test type done by P3B Arabiclecturers, the steps done to develop and to validate the learning achievement test, and the characteristics of the learning achievement test quality which theoretically analyzed. This survey research included 192 lecturers as the population who taught basic science and technology subject matters in semester gasal 2014/2015. 92 of them was established by using proportional random sampling technique as the sample. Documentation and questionnaire technique were used to collect data. The data collected was analyzed by using descriptive quantitative method.The result of this research shows that 1) 55,42% P3B UIN Suska Riau Arabic lecturers write essay test for measuring learning achievement, 13,03% writes objective test and 31,55% combines between essay and objective test; 2) in the developing processes test: 35,87% lecturers make the blue-print of test and 23,92% do not make it, while only 13,59% lecturers who make the new test and 2,74% lecturers used the last year test and there are 46,19% lecturers combined the last year test and the new test; 3) 54,89% lecturers recheck test and 3,73% do not do it, 25,50% lecturers recheck by themselves and 17,85% lecturers recheck together in group of the same subject matter and fully rechecked by 2,18% others lecturers, for rechecking of the esei test done by 32,85% lecturers whereas the obyective test rechecked by 11,18%, the aspect that most rechecked was the relevance between the test and the learning competence which done by 91% lecturers; and 4) theoretically, 87% the test done by lecturers are good related to the essence of test quality